2021
DOI: 10.3390/ijerph18020759
|View full text |Cite
|
Sign up to set email alerts
|

What Factors Help Young Children Develop Positive Perceptions of Their Motor Skills?

Abstract: A positive perception of motor skills is important for physical activity participation. The aim was to investigate which modifiable factors predict children’s perceived motor skills. Mothers completed questionnaires when their child was 3.5 and 5 years old. At 5 years old, the children’s perceived motor competence (PMC) was assessed. Separate linear regression models (up to 300 children) examined which factors at each time point predicted children’s PMC, adjusted for relevant confounders. Multivariate models w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…DCD does not only manifest itself on motor coordination difficulties, it has a widespread impact on different domains of functioning such as the cognitive, language, and social-emotional domains, which creates a challenge for good assessment [ 78 ]. Therefore, if indicated, a multidisciplinary approach is needed to disentangle primary and secondary underlying factors in children with DCD to understand the practical implications [ 75 , 79 ].…”
Section: Assessment and Treatment In Children With Dcdmentioning
confidence: 99%
“…DCD does not only manifest itself on motor coordination difficulties, it has a widespread impact on different domains of functioning such as the cognitive, language, and social-emotional domains, which creates a challenge for good assessment [ 78 ]. Therefore, if indicated, a multidisciplinary approach is needed to disentangle primary and secondary underlying factors in children with DCD to understand the practical implications [ 75 , 79 ].…”
Section: Assessment and Treatment In Children With Dcdmentioning
confidence: 99%
“…On the other hand, evidence shows that 4.4% of children aged 3 to 6 years have decreased developmental scores, and 8.8% are at risk of delay, and these decreased scores are associated with difficulties in achieving recommended levels of physical activity [ 1 ]. On the other hand, evidence indicates that children with higher levels of fundamental movement skills tend to be more active and perform more physical activity than those with poorer skills [ 44 ]. Recently, clear evidence has been found that physical activity decreases for each year of a child’s life, starting in early childhood [ 3 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%